Fluorescence virus-guided capturing system of human colorectal circulating tumour cells for non-invasive companion diagnostics. Issue 4 (28th May 2014) - Shigeyasu, Kunitoshi; Tazawa, Hiroshi; Hashimoto, Yuuri; Mori, Yoshiko; Nishizaki, Masahiko; Kishimoto, Hiroyuki; Nagasaka, Takeshi; Kuroda, Shinji; Urata, Yasuo; Goel, Ajay; Kagawa, Shunsuke; Fujiwara, Toshiyoshi
Abstract : Background: Molecular-based companion diagnostic tests are being used with increasing frequency to predict their clinical response to various drugs, particularly for molecularly targeted drugs. However, invasive procedures are typically required to obtain tissues for this analysis. Circulating tumour cells (CTCs) are novel biomarkers that can be used for the prediction of disease progression and are also important surrogate sources of cancer cells. Because current CTC detection strategies mainly depend on epithelial cell-surface markers, the presence of heterogeneous populations of CTCs with epithelial and/or mesenchymal characteristics may pose obstacles to the detection of CTCs. Methods: We developed a new approach to capture live CTCs among millions of peripheral blood leukocytes using a green fluorescent protein (GFP)-expressing attenuated adenovirus, in which the telomerase promoter regulates viral replication (OBP-401, TelomeScan). Results: Our biological capturing system can image epithelial and mesenchymal tumour cells with telomerase activities as GFP-positive cells. After sorting, direct sequencing or mutation-specific PCR can precisely detect different mutations in KRAS, BRAF and KIT genes in epithelial, mesenchymal or epithelial–mesenchymal transition-induced CTCs, and in clinical blood samples from patients with colorectal cancer. Conclusions: This fluorescence virus-guided viable CTC capturing method provides a non-invasive alternative to tissue biopsy or surgical resection of primary tumours for companion diagnostics.